Diagnosis Quest - Richard Morehead; Robert Fons (Association of American Medical Colleges, 2010)
Abstract Introduction Diagnosis Quest is a software program that simulates an ambulatory patient encounter. A patient problem is the departure point for assessing a student's skills in patient evaluation and diagnosis formulation through an open-ended learner-directed query approach. Methods The student begins by being introduced to the patient with basic information. A history is taken using a dialog box, and the exam is performed by selecting images. Special exams are accessed through linked files. Following this section, the student enters initial impressions on the differential diagnosis screen. This is followed by the lab and radiology sections, where the student orders from a menu. After viewing results, including actual radiographs, the student revisits his or her initial diagnostic impressions with the ability to order diagnostic pathology and specialist consultation. A final diagnosis is then entered. During this last step, a series of questions is posed to gauge the student's thought process. The case progresses as would a patient encounter, including the feature that the student has to decide to examine each part of the patient to gain access to the clinical data contained therein. After final diagnosis submission, the student is given the actual diagnosis in addition to expert feedback on best practices and subject review of the causative disease. Results The effectiveness of this project cannot be judged at this point as Diagnosis Quest has not yet been incorporated into the formal curriculum of the University of Kentucky College of Medicine. Discussion Producing excellent clinicians is the primary aim of the medical school curriculum. This tool allows a virtual experience with the autonomy an attending physician would enjoy and also permits mistakes to be made in a risk-free environment.